Non-Coding RNAs Associated With Radioresistance in Triple-Negative Breast Cancer - Aranza-Martínez, Alberto; Sánchez-Pérez, Julio; Brito-Elias, Luis; López-Camarillo, César; Cantú de León, David; Pérez-Plasencia, Carlos; López-Urrutia, Eduardo (Frontiers in Oncology, 2021)
The resistance that Triple-Negative Breast Cancer (TNBC), the most aggressive breast cancer subtype, develops against radiotherapy is a complex phenomenon involving several regulators of cell metabolism and gene expression; understanding it is the only way to overcome it. We focused this review on the contribution of the two leading classes of regulatory non-coding RNAs, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), against ionizing radiation-based therapies. We found that these regulatory RNAs are mainly associated with DNA damage response, cell death, and cell cycle regulation, although they regulate other processes like cell signaling and metabolism. Several regulatory RNAs regulate multiple pathways simultaneously, such as miR-139-5p, the miR-15 family, and the lncRNA HOTAIR. On the other hand, proteins such as CHK1 and WEE1 are targeted by several regulatory RNAs simultaneously. Interestingly, the study of miRNA/lncRNA/mRNA regulation axes increases, opening new avenues for understanding radioresistance. Many of the miRNAs and lncRNAs that we reviewed here can be used as molecular markers or targeted by upcoming therapeutic options, undoubtedly contributing to a better prognosis for TNBC patients.